Science and human behavior - Skinner, B.F. (Burrhus Frederic) 1904-1990 (New York The Free Press, 1965)
A detailed study of scientific theories of human nature and the possible ways in which human behavior can be predicted and controlled.
Section 1 : The possibility of a science of human behavior -- 1. Can science help? -- 2. A science of behavior -- 3. Why organisms behave -- Section 2 : The analysis of behavior -- 4. Reflexes and conditioned reflexes -- 5. Operant behavior -- 6. Shaping and maintaining operant behavior -- 7. Operant discrimination -- 8. The controlling environment -- 9. Deprivation and sanitation -- 10. Emotion -- 11. Aversion, avoidance, anxiety -- 12. Punishment -- 13. Function versus aspect -- 14. The analysis of complex cases -- Section 3 : The individual as a whole -- 15. "Self-control" -- 16. Thinking -- 17. Private events in a natural science -- 18. The self -- Section 4 : The behavior of people in groups -- 19. Social behavior -- 20. Personal control -- 21. Group control -- Section 5 : Controlling agencies -- 22. Government and law -- 23. Religion -- 24. Psychotherapy -- 25. Economic control -- 26. Education -- Section 6 : The control of human behavior -- 27. Culture and control -- 28. Designing a culture -- 29. The problem of control -- Index.
Keywords: Psychology; Behavior